Case report and literature review: Orally ingested toothpick perforating the lower rectum - Zhang, Xingliang; Xing, Mei; Lei, Shaoyang; Li, Wentao; Li, Zijin; Xie, Yibing; Zhu, Chenyu; Zhang, Shuqian (Frontiers in Surgery, 2024)
Introduction: Most foreign bodies (FBs) can spontaneously pass through the gastrointestinal tract. Sharp FBs are believed to puncture any part of the gastrointestinal tract, causing perforation and potentially secondary damage to adjacent organs.A 44-year-old male complained of having persistent dull pain in perianal region. He was diagnosed with a toothpick impacted into the wall of the lower rectum after accepting a digital rectal examination of lower rectum and a pelvic computed tomography (CT). The surgeon extracted the FB using a vascular forcep guided by the operator's index finger. The patient was discharged after having intravenous ceftriaxone for 6 days. A follow-up pelvic CT performed two weeks after surgery revealed the perirectal fat and muscles had already recovered as normal.A systematic review of relevant literature from the past decade was performed to summarize the imaging features of oral ingested toothpick perforating pass 删除[张淑倩]: even 删除[张淑倩]: conduct 删除[张淑倩]: extracting by 删除[张淑倩]: of 删除[张淑倩]: last 删除[张淑倩]: the gastrointestinal tract. The location of abdominal pain is an important clue for the diagnosis of toothpick perforation, and CT examination is recommended as the first option for detection of ingested toothpick. Determining the location of the toothpick perforation and assessing the severity of local inflammation are important basis for the selection of treatment.